Inhibitory effects of vinpocetine on sodium current in rat cardiomyocytes - Wei Yuan; Shi Nian-Ci; Zhong Ci-Sheng; Zheng Ping; Liang Zi-Jun (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of vinpocetine (Vin) on the sodium current (INa) in cardiomyocytes. METHODS: The sodium current in adult rat ventricular myocytes was measured by whole cell patch-clamp technique. RESULTS: The INa in cardiomyocytes was blocked reversibly by Vin, in concentration-dependent and voltage-dependent manner, but not rate- or use-dependent. The INa was attenuated by 13%-75% when the Vin concentration was raised from 10 to 80 mumol.L-1. The IC50 (95% confidence limits) was 36.4 (28.1-47.1) mumol.L-1. When the membrane potential depolarized over the range of -90 mV to +40 mV in 10-mV step, inhibitory effect of Vin on the INa was 39% at first, then maintained at a higher level, about 52% +/- 5%. The maximal depression (57%) reached at about 0 mV. Vin influenced both the activation and inactivation processes of sodium channel, and resulted in attenuation of the window currents (the slowly inactivating sodium currents). CONCLUSION: Vin inhibited sodium currents in rat ventricular myocytes.